ANALYSIS OF SCIENCE LITERACY LEARNING MEDIA DEVELOPMENT AS A FORM OF DIFFERENTIATED LEARNING IN PRIMARY SCHOOLS - Zahra, Siti Zahra Nur Solihat; Sri Utami, Irma Inesia (Sekolah Pascasarjana Universitas Ibn Khaldun Bogor, 2024)
The implementation of the independent curriculum through differentiated learning is a recommended strategy to be applied in learning in primary schools, because learning with this strategy refers to the needs and abilities of diverse learners. However, in its application, teachers must be able and precise in determining the appropriate teaching tools. Moreover, learning with the content of science literacy is an important thing to convey to students in the 21st century. So, this study aims to provide a literature review on the development of teaching media with science literacy content as a form of implementing differentiated learning in elementary schools. The literature review method was used to collect primary data from written sources such as journals, reports and other documents. The results of the study explain that the application of differentiated learning can be done after determining the suitability that refers to the needs and abilities of students. Based on this, the development of science literacy teaching media is a form of differentiated learning. The development of teaching media is needed because differentiated learning requires appropriate teaching media. So, it is important for teachers to continue to develop competence and be able to mature in implementing differentiated learning. It is hoped that the results of this literature review can provide a better understanding of the application of differentiated learning and improve students' science literacy competencies, especially for primary school teachers in the context of implementing an independent curriculum and fostering the character of students who can be competitive in the global world.